Watchdog - McIntosh, Will (New York Delacorte Press, 2017)
Orphaned and homeless, fourteen-year-old twins Vick and Tara, who is autistic, go up against a crime lord and her four-legged robotic army, with help from their robotic dog Daisy.
Keywords: Homeless teenagers -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; Robots -- Juvenile fiction; Criminals -- Juvenile fiction; Autism -- Juvenile fiction; Orphans -- Juvenile fiction; Homeless persons -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction; Robots -- Fiction; Criminals -- Fiction; Autism -- Fiction; Orphans -- Fiction; Science fiction; JUVENILE FICTION / Robots; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / Action & Adventure / General